Spontaneous Osteoclastogenesis, a risk factor for bone metastasis in advanced luminal A-type breast cancer patients - Fernández Vallone, Valeria; Borzone, Francisco Raúl; Martinez, Leandro Marcelo; Giorello, María Belén; Choi, Hosoon; Dimase, Federico; Feldman, Leonardo; Bordenave, Raúl Horacio; Chudzinski-Tavassi, Ana Marisa; Batagelj, Emilio; Chasseing, Norma Alejandra (Frontiers in Oncology, 2023)
Osteolytic bone metastasis in advanced breast cancer stages are a major complication for patient´s quality life and a sign of low survival prognosis. Permissive microenvironments which allow cancer cell secondary homing and later proliferation are fundamental for metastatic processes. The causes and mechanisms behind bone metastasis in breast cancer patients are still an unsolved puzzle. Therefore, in this work we contribute to describe bone marrow pre-metastatic niche in advanced breast cancer patients. We show an increase in osteoclasts precursors with a concomitant imbalance towards spontaneous osteoclastogenesis which can be evidenced at bone marrow and peripheral levels. Pro-osteoclastogenic factors RANKL and CCL-2 may contribute to bone resorption signature observed in bone marrow. Meanwhile, expression levels of specific microRNAs in primary breast tumors may already indicate a pro-osteoclastogenic scenario prior to bone metastasis. The discovery of prognostic biomarkers and novel therapeutic targets linked to bone metastasis initiation and development are a promising perspective for preventive treatments and metastasis management in advanced breast cancer patients.